(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Expansive soils swell laterally as well as vertically. Lateral volume changes will be accommodated by the cracks and fissures if there are cracks and fissures in the soil mass. However, when there are no cracks or the cracks are very small and close up without accommodating all of the volume increase that is required by the expansive soil, the swelling soil becomes restrained in the lateral directions. The result of this restrained case is the development of a lateral swelling pressure. In well compacted high plasticity clay fills, the process of swelling is likely to continue for many years. Thus, classical methods cannot be used to estimate the lateral pressure of expansive soils behind a retaining structure. In this study, a new finite element modeling of swelling behavior of expansive soil is made by using an analogy between the thermal expansion of the solid material and swelling of the expansive soil. Soil suction profiles for the driest and the wettest steady-state conditions are produced by using static soil suction theory. Thus, a suction envelope can be produced. The validity and applications of the study are investigated by considering several experimental works. Then, some hypothetical considerations that depend upon moisture changes in expansive soil, and in cohesive non-swelling soil (CNS) with different thicknesses and geometries as the backfill behind a retaining stmcture have been analyzed. The parameters that affect the transmitted lateral pressure on retaining stmctures are investigated. The results from the numerical modeling compare closely with the results of large-scale laboratory tests. The results also show that the swelling behavior of expansive soils is dependent upon soil suction change of the soil media.